The Commodification of Feminism — A Critical Analysis of Neoliberal Feminist Discourse - Sarah Louise Bennett (Studies in Social Science & Humanities, 2024)
This paper critically examines the commodification of feminism within the framework of neoliberal feminism, a discourse that has gained significant traction in recent years. Neoliberal feminism emphasizes individual empowerment, personal success, and market-driven solutions to gender inequality. While this approach has succeeded in making feminist ideas more mainstream and accessible, it also poses substantial challenges by overlooking systemic and structural barriers that many women face. This paper explores the historical emergence of neoliberal feminism, its key characteristics, and the role of media and corporations in promoting commodified feminist ideals. It further analyzes the positive and negative impacts of neoliberal feminism on broader feminist movements, highlighting the shift from collective action to individual empowerment. Through critical perspectives from radical, intersectional, and socialist feminists, this paper underscores the limitations of neoliberal feminism and calls for a renewed focus on collective action, intersectionality, and systemic change to achieve true gender equality. By resisting the commodification of feminist ideals and advocating for more inclusive strategies, the feminist movement can better address the root causes of gender inequality in a neoliberal context.